Penerapan Model Flipped Classroom Dalam Pembelajaran Daring Untuk Meningkatkanhasil Belajar Matematika - Meirita (Prosiding Temu Ilmiah Nasional Guru, 2022)
The Covid 19 pandemic has had an extraordinary impact on changing habits in every area of ​​life, including in the field of education. One alternative solution to overcome the weaknesses of online learning is to use the flipped classroom learning model. The purpose of this study was to find out the learning outcomes of students who were taught using the flipped classroom model in online learning to improve mathematics learning outcomes in trigonometry material in class X MIPA 2 students at SMAN 4 Cilegon semester II 2020/2021 academic year. Data collection techniques were carried out through tests and non-tests. Data analysis techniques in this study used descriptive comparative and qualitative descriptive techniques. The results showed that before the action research was carried out the average value of the daily assessment was 62.94 and the classical completeness was 38%. After conducting research actions with the application of the flipped classroom model in online learning in the mathematics subject trigonometry material in cycle I the average daily assessment value became 70.74 classical completeness became 74%. In cycle II, the average value of students' daily assessments was 76.47 and classical completeness was 91%.